The Factors Affecting Students’ Difficulties in Conducting Thesis at English Language Educational the University of Batanghari Jambi - Fitria Inda Yani; Suyadi Suyadi; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2022)
This research was included in quantitative research which aims to find out the problems and factors experienced by students so that it affects their difficulties in completing the thesis. The subjects of this study were 19 students of the 2018 English Department of Batanghari Jambi University who had completed their thesis. This research collected data through questionnaires distributed online using Google form. In this research, three main factors are identified that affecting undergraduate thesis writing. First, psychological factors which include self-esteem, anxiety, and motivation. Furthermore, the second factor is socio-cultural factors which include the social distance among each student and the social distance between students and supervisors. Lastly, linguistic factors which include domain error analysis and extent of error analysis. The results showed that psychology factors got a percentage of 40.36%, socio-cultural factors got a percentage of 29.66%, and linguistic factors got a percentage of 29.96%. Thus, it can be concluded that the most influencing factor in the difficulty of students completing the thesis is the psychological factor.